Analisis Pengaruh Keterbukaan Ekonomi Terhadap Pertumbuhan Ekonomi di Indonesia - Zebua, Merlin Kristin; Idris, Idris (Jurnal Kajian Ekonomi dan Pembangunan, 2024)
This research aims to determine and analyze the influence of economic openness on economic growth in Indonesia. This research uses time series data from 1993-2023 sourced from the Central Statistics Agency, Bank Indonesia, Bank International For Settlements, and World Bank. The results of the study reveal that (1) trade openness has a negative and significant effect on economic growth in Indonesia, (2) Foreign Investment and the real exchange rate have a positive effect, (3) The real exchange rate has a negative and insignificant effect on economic growth in Indonesia.